Polygyny and Farm Households' Resilience to Climate Shocks - Dessy, Sylvain; Tiberti, Luca; Tiberti, Marco; Zoundi, David (World Bank, Washington, DC, 2021)
Climate change and weather shocks pose major challenges for household income security and well-being, especially for smallholder farmers’ communities. In such communities, imperfect risk insurance and labor markets may induce households to use traditional institutions such as polygyny to harness their size and composition to their resilience strategies against these shocks. This paper tests this hypothesis by analyzing how polygyny’s interaction with droughts affects crop yields. For identification, the paper relies on the spatial variation in polygyny’s prevalence across Mali’s rural communes and the randomness of drought episodes. The findings show that polygynous communities are more resilient to drought-induced crop failure. Exploration of the mechanisms shows that polygynous communities diversify their income sources more than monogamous ones, including via child marriage—a phenomenon known to undermine women’s outcomes. As the literature links polygyny to underdevelopment, interventions to eliminate it should make formal resilience and adaptation strategies available to drought-prone communities. Failure to do so may entrench political opposition to enforcing a ban on polygyny and child marriage.